A generalization of a theorem of Arrow, Barankin and Blackwell to a nonconvex case. (3rd May 2016) - Kasimbeyli, Nergiz; Kasimbeyli, Refail; Mammadov, Musa
Abstract : The paper presents a generalization of a known density theorem of Arrow, Barankin, and Blackwell for properly efficient points defined as support points of sets with respect to monotonically increasing sublinear functions. This result is shown to hold for nonconvex sets of a partially ordered reflexive Banach space.